Analysis of phenolic compounds and antioxidant activity of methanolic extracts from inflorescences of Carduus sp. (June 2019) - Kozyra, Małgorzata; Komsta, Łukasz; Wojtanowski, Krzysztof
Graphical abstract: Highlights: establishment of the total phenolic content and antioxidant potential of the Carduus extracts. investigation of the possible correlation between phenolic compounds content and Carduus sp. Variety. chemometric analysis allowed to extract four independent trends in the content of identified phenolic compounds. Abstract: In the present study, the phenolic compounds in 70% (v/v) methanol extracts from the inflorescences of Carduus carlinoides Gouan, Carduus nigrescens Vill, Carduus defloratus L., Carduus nutans L., and Carduus crispus Gouan were identified. The extracts were tested by the RP-HPLC and HPLC/ESI-QTOF/MS methods. Flavonoids and phenolic acids were extracted from the inflorescences by ASE. HPLC profiles (fingerprints) of methanolic Carduus sp. extract were correlated with flavonoid and phenolic acid content by using chemometric methods. The obtained results revealed that various species showed characteristic profiles of phenolic acids and flavonoids. These compounds included nine flavonoids (isorhamnetin-3-glucoside, kaempferol-3-rhamnoglucoside, luteolin-7-glucoside, luteolin-7-glucuronide, apigenin-7-glucoside, kaempferol-3-rutinoside, kaempferol-3-rhamnoglucoside, apigenin, and luteolin) and five phenolic acids (neochlorogenic, chlorogenic, caffeic, protocatechuic, and p- hydroxybenzoic acids). Also the evaluation of antioxidant activity of 70% (v/v) methanolic extracts, which was expressed both as a percentage of DPPH radical inhibition and EC50 values (mg/mL). The EC50 values for all obtained extracts were as follows: C. nutans (EC50 = 0.46 mg/mL), C. carlinoides (EC50 = 0.60 mg/mL), C. crispus (EC50 = 0.70 mg/mL), C. nigrescens (EC50 = 0.78 mg/mL), and C. nigrescens (EC50 = 0.80 mg/mL). Chemometric analysis of the RP-HPLC chromatograms allowed to extract four independent trends in the content of the identified components. The most identical extracts came from two species: C. nigrescens and C . deccusatus.